Degradation Characteristics of Wood Using Supercritical Alcohols - Jeeban Poudel; Sea Cheon Oh (Energies, 2012)
In this work, the characteristics of wood degradation using supercritical alcohols have been studied. Supercritical ethanol and supercritical methanol were used as solvents. The kinetics of wood degradation were analyzed using the nonisothermal weight loss technique with heating rates of 3.1, 9.8, and 14.5 °C/min for ethanol and 5.2, 11.3, and 16.3 °C/min for methanol. Three different kinetic analysis methods were implemented to obtain the apparent activation energy and the overall reaction order for wood degradation using supercritical alcohols. These were used to compare with previous data for supercritical methanol. From this work, the activation energies of wood degradation in supercritical ethanol were obtained as 78.0–86.0, 40.1–48.1, and 114 kJ/mol for the different kinetic analysis methods used in this work. The activation energies of wood degradation in supercritical ethanol were obtained as 78.0–86.0, 40.1–48.1, and 114 kJ/mol. This paper also includes the analysis of the liquid products obtained from this work. The characteristic analysis of liquid products on increasing reaction temperature and time has been performed by GC-MS. The liquid products were categorized according to carbon numbers and aromatic/aliphatic components. It was found that higher conversion in supercritical ethanol occurs at a lower temperature than that of supercritical methanol. The product analysis shows that the majority of products fall in the 2 to 15 carbon number range.